THE PHILOSOPHY OF POLITICAL LIBERALISM, THE GLOBAL ORDER AND THE QUESTION OF JUSTICE (2011)
The issue of transnational justice was made popular in the 20th century by the American liberal philosopher, John Bordley Rawls, who tries to evolve a conception of justice that would be applicable at the transnational level. Unfortunately, his liberal prescription for transnational justice does not provide for any principle of redistributive justice that would be morally obligatory at the international level and, as such, fails to adequately address the question of justice at that level. This study, therefore, proposed a theoretical model that would have an ethical basis for transnational redistributive justice and, thus, facilitate the evolution of a just and harmonious global order. The model of deliberative cosmopolitan democracy, which combines the strengths of two transnational democratic theories: Deliberative Democracy and Cosmopolitan Democracy, constituted the framework for this study. The work adopted the conceptual, analytical and reconstructive methods of philosophy. The conceptual approach was employed to clarify the concepts of global order, justice, democracy and other key terms related to the question of transnational justice. The study critically examined the theory of political liberalism to show its inadequacies and argue for its reconstruction to ensure the institution and promotion of transnational justice. The sources of data were mainly library and archival based. Rawls’ A Theory of Justice, Political Liberalism, The Law of Peoples and other relevant texts constituted our data for this study. These are the core texts that have dealt with the question of democracy and justice at the transnational level. Rawls’ liberal internationalism extends to the transnational level his earlier development of the theory of justice but it does not adequately address the question of justice at the international level: it does not extend the difference principle-the distributive principle that stipulates that the distribution of social wealth and income should be done in a way that favours the socially worst offs-to the transnational level. The duty of assistance it introduced, instead, is morally supererogatory and has not addressed the question of distributive justice at the international level in a morally obligatory manner. Furthermore, his proposal is silent on the present international economic order that favours the developed economies more than the developing ones. The model of deliberative cosmopolitan democracy, which combines the strengths of Deliberative Democracy and Cosmopolitan Democracy, provides a better philosophy because it promotes the distributive, deliberative and institutional ideals of global justice. It proposes the principle of extensive democratic autonomy at the national level and a deliberative cosmopolitan democratic law at the transnational level. The principle and the law extensively protect the right to self-determination of peoples and also guarantee justice among nation-states and peoples. Transnational justice is attainable through the ideals of deliberative cosmopolitan democracy. This model has a better prospect of realising the goal of transnational justice than Rawls’ liberal internationalism on account of its distributive, deliberative and institutional features that are fundamental to the entrenchment of global justice. This would constitute a good foundation upon which to establish an enduring stability and peace in the global arena.